2015
DOI: 10.1002/celc.201500268
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Degradation of Multiwall Carbon Nanotubes at High Anodic Potential for Oxygen Evolution in Acidic Media

Abstract: There is great interest in electrochemical water splitting for the efficient utilization of sustainable energy. As an alternative to high-priced materials, carbon offers considerable potential. However, carbon is limited as an electrode material for the oxygen evolution reaction (OER), owing to its thermodynamic instability against electrochemical oxidation. In this study, we investigated the electrochemical degradation of multiwall carbon nanotubes (MWCNTs) under the acidic OER environment. Electrochemical ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
96
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(102 citation statements)
references
References 43 publications
4
96
0
2
Order By: Relevance
“…Different water electrolysis technologies are currently discussed as options to handle intermittent electricity supply originating from renewable energy sources [54,55]. Final disclosure (if any) about the "best" technology can be only answered in the system framework where the whole pathway from raw water to pressurized hydrogen, including all pre-and post-processing steps, has to be considered.…”
Section: From the Catalyst To The Water Electrolysis Cellmentioning
confidence: 99%
See 1 more Smart Citation
“…Different water electrolysis technologies are currently discussed as options to handle intermittent electricity supply originating from renewable energy sources [54,55]. Final disclosure (if any) about the "best" technology can be only answered in the system framework where the whole pathway from raw water to pressurized hydrogen, including all pre-and post-processing steps, has to be considered.…”
Section: From the Catalyst To The Water Electrolysis Cellmentioning
confidence: 99%
“…Additionally, catalyst layers should provide sufficiently high ionic and electronic conductivities. All these requirements are difficult to satisfy using current methods for catalyst layer preparation, which often lead to low catalyst utilization, and thus the necessity to use high catalyst loadings which contribute significantly to the electrolyser cost [54]. For this reason, the development of novel strategies for the preparation of tailor-made high-performance catalyst layers has very high practical relevance.…”
Section: From the Catalyst To The Water Electrolysis Cellmentioning
confidence: 99%
“…[31,32] Electrochemical degradation of MWCNTs induces both structural and physico-chemical changes such as surface defects and oxidation. [31,34] In summary, improved electrochemical performance can be observed when measuring ORR activity for extremely high specific surface area carbon nanomaterials but they are most likely accompanied by quick changes of the surface and degradation. In contrast, high specific surface area carbon nanomaterials suffer from much higher degradation rates.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, relatively slow kinetics and high loadings of cheap carbon allow them to be used as electronic interconnects. [31][32][33][34][35][36] However, reaction pathways and active sites depend heavily on the environment of the catalyst, such as acidity of the electrolyte, temperature, the presence of water etc. [33] The formation of hydrogen peroxide and the oxidation of the carbon nanomaterial generates charge carriers and might be mistaken for ORR activity.…”
Section: Introductionmentioning
confidence: 99%
“…

No metal needed: A core-shell-like carbon catalyst consisting of a few layers of nitrogen-doped graphite on a carbon black core was prepared by pyrolyzing an ionic liquid (IL) with carbon black (CB) particles. [10][11] In 2016, the Xu group reported that a nitrogen, phosphorus and oxygen triply-doped/functionalized carbon cloth was active and stable for OER in acid solution. The resilience of the catalyst in acid solution is due to the greater protection of the nitrogen-containing OER active sites in a graphitic shell.

…”
mentioning
confidence: 99%